Comparison of Personality Factors among People with Substance Dependence Disorder and non-addicted People - Nooripour, Mojtahedi, Habibi, Soveyzi (Journal of Educational, Health and Community Psychology, 2015)
Abstract Prescription of drug abuse is an important and significant world issue. This study aims to compare sixteen personality factors among patients with substance abuse disorder and normal people. The research method wasÂ ex postÂ facto and statistical population consisted of two groups of addicted individuals and normal individuals in Tehran. 100 addicted patients were selected by convenient sampling method among patients who had referred to addiction treatment centers in Tehran. The control group with 100 people was selected from normal people. Research instruments includedÂ Cattellâs Sixteen Personality Factor Inventory (16PF) and the collected data was analyzed using ANOVA. Findings revealed that there are significant differences in factor A, factor C, factor E, factor F, factor G, factor H, factor I, factor L, factor M, factor N, factor O, factor Q1, factor Q2, factor Q3, and factor Q4 among addicted and healthy groups. It is concluded that an awareness of the effects of personality factors on substance abuse can help to decrease, or even prevent, addiction disorder.Â Key words: addiction, personality factors, substance dependence disorder